Calcium-Phosphate Biomineralization Induced by Alkaline Phosphatase Activity in Escherichia coli: Localization, Kinetics, and Potential Signatures in the Fossil Record - Cosmidis, Julie; Benzerara, Karim; Guyot, François; Skouri-Panet, Fériel; Duprat, Elodie; Férard, Céline; Guigner, Jean-Michel; Babonneau, Florence; Coelho, Cristina (Frontiers in Earth Science, 2015)
Bacteria are thought to play an important role in the formation of calcium-phosphate minerals composing marine phosphorites, as supported by the common occurrence of fossil microbes in these rocks. Phosphatase enzymes may play a key role in this process. Indeed, they may increase the supersaturation with respect to Ca-phosphates by releasing orthophosphate ions following hydrolysis of organic phosphorus. However, several questions remain unanswered about the cellular-level mechanisms involved in this model, and its potential signatures in the mineral products. We studied Ca-phosphate precipitation by different strains of Escherichia coli which were genetically modified to differ in the abundance and cellular localization of the alkaline phosphatase (PHO A) produced. The mineral precipitated by either E. coli or purified PHO A was invariably identified as a carbonate-free non-stoichiometric hydroxyapatite. However, the bacterial precipitates could be discriminated from the ones formed by purified PHO A at the nano-scale. PHO A localization was shown to influence the pattern of Ca-phosphate nucleation and growth. Finally, the rate of calcification was proved to be consistent with the PHO A enzyme kinetics. Overall, this study provides mechanistic keys to better understand phosphogenesis in the environment, and experimental references to better interpret the microbial fossil record in phosphorites.